Our Board, Our Rules: Nonconformity to Global Corporate Governance Norms - Witt, Michael A.; Fainshmidt, Stav; Aguilera, Ruth V. (Administrative Science Quarterly, 2022)
What drives organizational nonconformity to global corporate governance norms? Despite the prevalence of such norms and attendant conformity pressures, many firms do not adhere to them. We build on a political view of corporate governance to explore how different national institutional contexts and organizational conditions combine to produce over- and underconformity to global board independence norms. Using configurational analyses and data from banks in OECD countries, we identify multiple equifinal combinations of conditions associated with over- and underconformity. We also find that over- and underconformity have different drivers. We conjecture that while overconformity is associated with a shareholder–management coalition in liberal market economies, underconformity results from multiple complex combinations of national and organizational conditions that often include dominant blockholders, strong labor rights, and small organizational size. We leverage these findings to abduct theoretical insights on nonconformity to global corporate governance norms. Doing so sheds light on the role of power in conditioning the adoption of global practices and contributes to research on international corporate governance by informing discourse surrounding the globalization of markets.